Serosurvey for Nipah virus in bat population of southern part of India. (June 2022) - Gokhale, Mangesh; Sudeep, A.B.; Mathapati, Basavaraj; Balasubramanian, R.; Ullas, P.T.; Mohandas, Sreelekshmy; Patil, Dilip R.; Shete, Anita M.; Gopale, Sanjay; Sawant, Pradeep; Jain, Rajlaxmi; Holeppanavar, Manjunath; et al.
Abstract: Nipah virus (NiV) is one of the priority pathogens with pandemic potential. Though the spread is far slower than SARS-CoV-2, case fatality is the biggest concern. Fruit bats belonging to genus Pteropus are identified to be the main reservoir of the virus causing sporadic cases and outbreaks in Malaysia, Bangladesh and India. The sudden emergence of Nipah in Kerala, India during 2018–2019 has been astonishing with respect to its introduction in the unaffected areas. With this, active Nipah virus surveillance was conducted among bat populations in Southern part of India viz., Karnataka, Kerala, Tamil Nadu, Telangana, Puducherry and Odisha during January-November 2019. Throat swabs/rectal swabs (n = 573) collected from Pteropus medius and Rousettus leschenaultii bat species and sera of Pteropus medius bats (n = 255) were screened to detect the presence of Nipah viral RNA and anti-Nipah IgG antibodies respectively. Of 255  P. medius bats sera samples, 51 bats (20%) captured from Karnataka, Kerala, Tamil Nadu and Puducherry demonstrated presence of anti-Nipah IgG antibodies. However, the presence of virus couldn't be detected in any of the bat specimens. The recent emergence of Nipah virus in Kerala in September 2021 warrants further surveillance of Nipah virus among bat populations from the affected and remaining states of India.